New kid on the block - Prelutsky, Jack (Greenwillow books New York, 1984)
Humorous poems about such strange creatures and people as Baloney Belly Billy and the Gloopy Gloppers.
6 - 10 years
Keywords: Humorous poetry; Children's poetry -- American